Mannan based prebiotics modulate growth rate and energy phenotype of tetracycline resistant E. coli - Grant, Sharon; Smith, Helen; Murphy, Richard (Frontiers in Animal Science, 2023)
Unsustainable antimicrobial use in industrial agriculture has contributed to the rise in antimicrobial resistance and there is an urgent need to find alternative and more sustainable strategies to traditional antimicrobials. Prebiotics, such as mannan-rich fraction (MRF), a cell wall product from Saccharomyces cerevisiae, have demonstrated an ability to alter the growth of antibiotic susceptible and resistant Escherichia coli and improve the efficacy of antibiotics through modulation of cellular activity. In this study the impact of mannan based prebiotics on growth and respiration of E. coli was assessed by observing microbial growth, oxygen consumption rate and extracellular acidification rate in the presence and absence of tetracycline. The findings further demonstrate the capabilities of MRF with respect to improving microbial antibiotic sensitivity, particularly in resistant strains. This potentially enables a more efficient control of resistant pathogens with food safety implications and promotion of more sustainable use of antibiotics in animal production systems.